2011
DOI: 10.1186/1472-684x-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Palliative inpatients in general hospitals: a one day observational study in Belgium

Abstract: BackgroundHospital care plays a major role at the end-of-life. But little is known about the overall size and characteristics of the palliative inpatient population. The aim of our study was to analyse these aspects.MethodsWe conducted a one-day observational study in 14 randomly selected Belgian hospitals. Patients who met the definition of palliative patients were identified as palliative. Then, information about their socio-demographic characteristics, diagnoses, prognosis, and care plan were recorded and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
(36 reference statements)
4
18
1
3
Order By: Relevance
“…This figure is comparable with those of other studies, even though there are differences between studies due to methodological differences [12,17,20,23]. In a study in a New Zealand Hospital, 9.2% of cancer patients were assessed to have a palliative care need [23], whereas the corresponding figure in general hospitals in Belgium was 4.8% [12].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This figure is comparable with those of other studies, even though there are differences between studies due to methodological differences [12,17,20,23]. In a study in a New Zealand Hospital, 9.2% of cancer patients were assessed to have a palliative care need [23], whereas the corresponding figure in general hospitals in Belgium was 4.8% [12].…”
Section: Discussionsupporting
confidence: 79%
“…However, hospitals are not ideal settings for palliative care patients, as lack of staff and increased time pressure are common problems [10], and the emotional strain of caring for palliative patients can be a challenge [11]. Moreover, healthcare professionals first need to recognize patients as being Bpalliative^and then need to have a readiness to discuss optimal, not maximal, care during their hospitalization [12].…”
Section: Introductionmentioning
confidence: 99%
“…8 A more recent study in 2011 reported that just 9.4% of hospital patients in Belgium were identified as having palliative care needs. 23 All of these studies used the subjective judgement of generalist medical and nursing staff to identify patients with palliative care need, rather than an objective measure based on diagnostic criteria. Our results show that when using a systematic and objective measure, the percentage of patients with identified need is much higher and represents a substantial proportion of the inpatient population.…”
Section: Discussionmentioning
confidence: 99%
“…123 In a census undertaken in 2001, Gott and colleagues 124 reported that 23% of hospital inpatients were identified as having palliative care needs. A more recent study in 2011 22 reported that just 9.4% of hospital patients in Belgium were identified as having palliative care needs (although this study excluded intensive care units and palliative care units). All of these studies used the subjective judgement of generalist medical and nursing staff to identify patients with palliative care need, rather than an objective measure based on diagnostic criteria, as used in this study.…”
Section: Extent Of Palliative Care Needmentioning
confidence: 99%
“…21 A more recent study in 2011 reported that 9.4% of hospital patients in Belgium were identified as having palliative care needs. 22 However, both of these studies used the subjective judgement of ward-based medical and nursing staff to identify patients with palliative care needs, rather than using an objective measure.…”
Section: The Uk Policy Contextmentioning
confidence: 99%